Cholecystokinin-dopamine coexistence: electrophysiological actions corresponding to cholecystokinin receptor subtype - Hommer, DW (J Neurosci, 1986)
Cholecystokinin (CCK)-like peptides when administered intravenously produce 2 distinct actions on the single-unit activity of mesencephalic dopamine (DA) neurons in the rat: an excitatory action and a potentiation of the inhibitory effects of DA agonists. The ability of several CCK fragments that have been shown to bind selectively to the peripheral and/or the central CCK-binding sites were examined for their ability to induce either excitation or a potentiation of DA. Only sulfated CCK-8 was able to induce excitation of mesencephalic DA neurons, but both sulfated and unsulfated CCK-8, as well as CCK-4, potentiated the inhibitory effects of the DA agonist apomorphine (APO). CCK-3 failed to potentiate APO-induced inhibition. Both of these effects appeared to be confined to cell bodies in regions of the ventral tegmental area and substantia nigra, zona compacta that have been reported to contain both DA and CCK. Thus, CCK-like peptides that have been shown to bind to the high-affinity CCK binding site in brain potentiated the effects of DA. In contrast, the ability of CCK-like peptides to induce neuronal excitation corresponds with their affinity for the peripheral-type CCK binding site.